Gema Muharram di Kudu Gantiang Barat: Menguatkan Nilai Keislaman Lewat Lomba Edukatif dan Kreatif - Riya Fatmawati; Allya Putri Rinjani; Flora Hardani; Ilham Yusda; Syarfina Salnah; Tri Sovanialinsi (CV. ITTC INDONESIA, 2025)
This community service activity stems from the limited variety of religious guidance for children in Nagarı Kudu Gantiang Barat which has not fully provided space for the development of creativity, self-confidence, and meaningful religious learning experiences, despite having a high level of religiosity and a strong tradition of surau-based Islamic education. This study aims to describe the implementation of the Gema 1 Muharram activity and analyze its impact in strengthening Islamic values and character building of children through educational and creative competition activities. The method used is a descriptive qualitative approach in the context of community service carried out by students of the Real Work Lecture (KKN) of Padang State University. The analysis technique is carried out through direct observation during the activity, supported by documentation in the form of photos and videos, as well as informal interviews with competition participants, parents, TPA/MDA teachers, and religious leaders, then analyzed descriptively using source triangulation to increase data validity. The results of the study indicate that the adhan competition, Musabaqah Tilawatil Qur'an (MTQ), and Al-Quran memorization activities are able to improve children's religious abilities. fostering self-confidence, discipline, and religious attitudes, as well as strengthening social solidarity and community participation in children's religious development, so that the Gema 1 Muharram activity can be seen as a good practice of community service that integrates religious values, character education, and local wisdom harmoniously.